ANALISIS PERBEDAAN ATENSI VISUAL CUSTOMER SHOPEE TERHADAP PRODUK FLASH SALE DENGAN PRODUK NORMAL BERBASIS EYE TRACKING - Zabbrina Ayu Marcellina Tanjung; Dita Sari Vita L.S; Monalisa Br Sembiring Depari; Evta Indra; Deni Adha Akbari; Rizki Edmi Edison (Politeknik Bisnis Indonesia, 2024)
Shopee is known as the e-commerce platform that is most widely used by people in Indonesia. One of the advantages offered by this platform is flash sales on various products at certain times. This study aims to determine the visual attention patterns of shopee users when viewing websites with flash sale captions using eye tracker technology. A total of 63 participants who were divided into two groups based on their experience using shopee were shown four types of products, each of which had a flash sale display and a normal display. There were five regions of interest in each display and two types of functions, first time fixation and Dwell time, were analyzed. This study shows that even though the longest duration was used by participants to view the flash sale description region, the first region viewed by both groups of participants was the product region. We hope that this data can be a reference for e-commerce platform website design to increase attention to the main message.